Edukasi Pada Ibu Balita Tentang Pentingnya Pemberian Munisasi Dasar Pada Bayi Di Kec. Panai Tengah Kab. Labuhanbatu Tahun 2023 - Nadya Fitriani (STIKES Columbia Asia Medan, 2023)
Immunization is the most effective and efficient public health effort in preventing disease and reducing death rates. This study aims to determine the factors that influence the provision of basic immunizations to babies at the PT Pratama Clinic. Hijau Pryan Perdana 2023. The number of samples used was 35 people obtained using total sampling techniques. The data analysis technique uses chi square. The results obtained in this study were that the majority of respondents did not complete basic immunization, 22 people (62.9%), there was a relationship between the age variable with a value of p = 0.004, there was a relationship with the education variable with a value of p = 0.012, there was a relationship with the employment variable with a value of p = 0.036, there is a relationship between the knowledge variable with a value of p = 0.003, there is a relationship between the family support variable with a value of p = 0.010 with the provision of basic immunization. There is a relationship between maternal age, maternal education, maternal employment, maternal knowledge and family support with providing basic immunizations to babies. It is recommended for health services to increase mothers' knowledge about basic immunization for babies through education to increase the completeness of basic immunization for babies.